The essential Reinhold Niebuhr : selected essays and addresses - Niebuhr, Reinhold, 1892-1971 (Yale University Press, 1986)
"Theologians, ethicist, and political analyst, Reinhold Neiburh, was a towering figure of twentieth-century religious thought. In this important book, the best of Neiburh's essays have been brought together for the first time. Selected, edited, and introduced by Robert McAffee Brown - a student and friend of Nieburh's and himself a distinguished thoelogian - the works included here testify to the brilliant polemics, incisive analysis, and deep faith that characterized the whole of Neibuhr's life"--Back cover